Registro de alimentos com alegações de propriedades funcionais no Brasil: uma revisão - Mendes, Ana Júlia Rodrigues (Universidade Federal de São Carlos, 2023)
The functional food and beverage market has been growing in recent years due to the concern of consumers with health and quality of life. Therefore, food industries are increasingly investing in products that bring functional properties and health benefits, which are called functional foods. There are many bioactive compounds associated with beneficial effects on human health. Among them, dietary fiber, carotenoids, probiotics, and omega-3 fatty acids are highlighted. However, for food functionality claims to be presented on packaging and advertising, it is necessary to register the products. In Brazil, currently, Resolution N°. 18, of April 30, 1999, establishes the Basic Guidelines for the Use of Claims of Functional Properties and Health Properties in Foods, while Resolution N°. 19, of April 30, 1999, presents the Technical Regulation of Procedures for Registration of Food with Claims of Functional and/or Health Properties on its Labeling. In addition to these resolutions, there are many other documents issued by the National Health Surveillance Agency (ANVISA) to establish the guidelines that must be followed by companies wishing to apply for this registration. The volume of information and the way it is presented by regulatory agencies can make the process very difficult. Thus, the present work aimed to present the definitions related to functional foods and functionality claims, and to gather and clarify the documents and steps necessary for requesting the registration of functionality claims with ANVISA.
Registration of food with claims of functional propergies in Brazil: a review
Keywords: Alegações; Alimentos funcionais; Registro; ANVISA; Allegations; Functional foods; Registration; ANVISA; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::PADROES, LEGISLACAO E FISCALIZACAO DE ALIMENTOS